Governance and Policy Innovations for Food Security in a Buffer City: Causal Pathways and Evidence from Palopo, Indonesia - Novayanti Sopia Rukmana; Saddam Husain Tamrin; Tawakkal Baharuddin; Febrianto Syam (Journal of Contemporary Governance and Public Policy, 2026)
This study analyses the drivers of low food security in Palopo City, Indonesia, and proposes locally relevant policy options. As an autonomous buffer city that supports surrounding regions through food distribution and trade, Palopo remains under-examined in debates on food security governance. The study contributes by foregrounding the governance challenges facing buffer cities while aligning with SDG 2 (Zero Hunger), particularly Targets 2.1–2.5 and 2.a–2.c on ending hunger, improving nutrition, strengthening sustainable and climate-resilient food systems, increasing agricultural investment, and stabilising food markets. Using a qualitative descriptive design, the research draws on official documents, regional policy instruments, and peer-reviewed literature. Data were analysed systematically in NVivo 12 Plus through import, coding, relationship mapping, and visualisation to identify recurring patterns. The findings indicate that Palopo’s food security is constrained by limited local production, shrinking agricultural land, climate-related pressures on yields, weak distribution and logistics infrastructure, low purchasing power, and ineffective policy implementation. Inadequate logistics increase transport costs and contribute to price volatility, while poverty and food inflation restrict access to nutritious food. Policy priorities include boosting productivity via appropriate technologies and food diversification, upgrading distribution through technology-enabled logistics, strengthening purchasing power through food-based local economic programmes, and improving the targeting and effectiveness of subsidies and food assistance.